The collapse transition on superhydrophobic surfaces - Kusumaatmaja, H; Blow, M; Dupuis, A; Yeomans, J (2008)
We investigate the transition between the Cassie-Baxter and Wenzel states of a slowly evaporating, micron-scale drop on a superhydrophobic surface. In two dimensions analytical results show that there are two collapse mechanisms. For long posts the drop collapses when it is able to overcome the free-energy barrier presented by the hydrophobic posts. For short posts, as the drop loses volume, its curvature increases allowing it to touch the surface below the posts. We emphasise the importance of the contact line retreating across the surface as the drop becomes smaller: this often preempts the collapse. In a quasi-three-dimensional simulation we find similar behaviour, with the additional feature that the drop can depin from all but the peripheral posts, so that its base resembles an inverted bowl. © Europhysics Letters Association.